Repurposing ethyl bromopyruvate as a broad-spectrum antibacterial. (25th January 2019) - Kumar, Ajay; Boradia, Vishant Mahendra; Thakare, Ritesh; Singh, Alok Kumar; Gani, Zahid; Das, Swetarka; Patidar, Anil; Dasgupta, Arunava; Chopra, Sidharth; Raje, Manoj; Raje, Chaaya Iyengar
Abstract: Background: The emergence of drug-resistant bacteria is a major hurdle for effective treatment of infections caused by Mycobacterium tuberculosis and ESKAPE pathogens. In comparison with conventional drug discovery, drug repurposing offers an effective yet rapid approach to identifying novel antibiotics. Methods: Ethyl bromopyruvate was evaluated for its ability to inhibit M. tuberculosis and ESKAPE pathogens using growth inhibition assays. The selectivity index of ethyl bromopyruvate was determined, followed by time–kill kinetics against M. tuberculosis and Staphylococcus aureus . We first tested its ability to synergize with approved drugs and then tested its ability to decimate bacterial biofilm. Intracellular killing of M. tuberculosis was determined and in vivo potential was determined in a neutropenic murine model of S. aureus infection. Results: We identified ethyl bromopyruvate as an equipotent broad-spectrum antibacterial agent targeting drug-susceptible and -resistant M. tuberculosis and ESKAPE pathogens. Ethyl bromopyruvate exhibited concentration-dependent bactericidal activity. In M. tuberculosis, ethyl bromopyruvate inhibited GAPDH with a concomitant reduction in ATP levels and transferrin-mediated iron uptake. Apart from GAPDH, this compound inhibited pyruvate kinase, isocitrate lyase and malate synthase to varying extents. Ethyl bromopyruvate did not negatively interact with any drug and significantly reduced biofilm at a 64-fold lower concentration than vancomycin. When tested in an S. aureus neutropenic thigh infection model, ethyl bromopyruvate exhibited efficacy equal to that of vancomycin in reducing bacterial counts in thigh, and at 1/25th of the dosage. Conclusions: Ethyl bromopyruvate exhibits all the characteristics required to be positioned as a potential broad-spectrum antibacterial agent.